The Outcomes of Total Anomalous Pulmonary Venous Connection in Neonates−10-Year Experience at a Single Center - Ji, Erchao; Qiu, Hailong; Liu, Xiaobing; Xie, Wen; Liufu, Rong; Liu, Tao; Chen, Jimei; Wen, Shusheng; Li, Xiaohua; Cen, Jianzheng; Zhuang, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Recent developments in surgical techniques and hospital care have led to improved outcomes following repair of total anomalous pulmonary venous connection (TAPVC). However, surgical repair of neonatal TAPVC remains associated with a high risk of postoperative mortality and pulmonary venous obstruction (PVO). We conducted this retrospective study to identify risk factors associated with surgical outcomes in the neonatal population. Methods: A retrospective review was conducted for all 127 neonates who underwent operations for isolated TAPVC from January 2009 to January 2019. Results: Preoperative PVO occurred in 33 (26.0%) of the 127 patients. Fifty patients (39.4%) required tracheal intubation before the operation. Twenty-three patients (18.1%) underwent emergency surgery. There were 11 (8.7%) early deaths. Significant risk factors were prolonged cardiopulmonary bypass (CPB) time (p = 0.013) and increased postoperative central venous pressure (CVP, p = 0.036). There were 5 (4.3%) late deaths within 1 year of repair. The risk factors for overall death were preoperative acidosis (p = 0.001), prolonged CPB time (p < 0.001) and increased postoperative CVP (p = 0.007). In particular, mortality was significantly higher (p = 0.007) with a postoperative CVP > 8 mmHg. With an increase in use of sutureless techniques (p = 0.001) and decrease in deep hypothermic circulatory arrest (p = 0.009) over the past 5 years, postoperative mortality greatly decreased (21.2%: 6.7%, p = 0.016). Postoperative PVO occurred in 15 patients (11.8%). Risk factors were mixed TAPVC (p = 0.037), preoperative acidosis (p = 0.001) and prolonged CPB time (p = 0.006). Conclusion: Although postoperative mortality of neonatal TAPVC has dropped to 6.7% over the past 5 years, it is still relatively high. Risk factors for postoperative death include preoperative acidosis, prolonged CPB time and increased postoperative CVP. Mortality was significantly higher for neonates with an average CVP > 8 mmHg 24 h after surgery.